INVESTIGATION OF NON-CONFORMITY OF PRESENT AND BURIED RELIEFS AND IMPROVEMENT OF KARKACHUN WATERSHED BOUNDARIES (Proceedings of the YSU C: Geological and Geographical Sciences, 2007)
Unconformity of present and ancient volcanic constructions brings to specific distribution of ground water run off. Discrepancy of reliefs is found in northern, western and South-Western parts of Karkachun River basin. For ground water development purposes buried local watersheds are of most importance, mainly the territory bounded by Karnut, Arevik, Hovtashen, Geghanist and Jrarat settlements. The annual ground water run off of this area is calculated about 41,5 million cubic meters.
Keywords: Karkachun River basin; ground water; buried local watersheds